Interval shrinkage estimation of two-parameter exponential distribution with random censored data - Ali Soori; Parviz Nasiri; Mehdi Jabbari Nooghabi; Farshin Hormozinejad; Mohammadreza Ghalani (Journal of Mahani Mathematical Research)
The use of the two-parameter exponential distribution model in fitting survival and reliability analysis data in the presence of censored random data has recently attracted the attention of a large number of authors. Considering the importance of the model, its parameter estimation is discussed using the method of moment, maximum likelihood and shrinkage estimation. To present the interval shrinkage estimator, it is first proved that the moment estimators are asymptotically unbiased and the interval shrinkage estimator performs better compared to other estimators. Finally, using two real data sets and statistical criteria, the goodness of fit of the model is compared with censored random data based on parameter estimation methods.